The Problem of Polypharmacy in Female Patients with Overactive Bladders – Cross-Sectional Study in a Specialist Outpatient Department - Schneidinger, C. S.; Umek, W.; Böhmdorfer, B. (Geburtshilfe und Frauenheilkunde, 2016)
Background: The consumption of certain drugs can cause urinary incontinence. The aim of this study is to determine the frequency of consumption of drugs that can favour incontinence, the incidence of polypharmacy and the incidence of potentially dangerous drug-drug interactions in female patients suffering from overactive bladder (OAB) who presented to a urogynaecological outpatient department. Methods: We undertook a retrospective case series study. The data from 100 female patients who attended the urogynaecological outpatient department of the Vienna General Hospital [VGH; Allgemeinen Krankenhauses Wien (AKH)] in the period from 20. 07. 2010 to 30. 08. 2011 were evaluated. The patients suffered either from an OAB or mixed incontinence with predominantly urge components. Among other factors, we were interested in the drugs taken for longer periods of time as well as the general and the urogynaecological case histories. 15 parameters were recorded: age, BMI, menopausal status, parity, pelvic organ prolapse, DIAPPERS criteria (delirium, infection (urinary), atrophic urethritis and vaginitis, pharmaceuticals, psychological disorders (especially depression), excessive urine output, restricted mobility, stool impaction), drug side effects and drug-drug interactions. A descriptive statistical analysis was performed. The drugs were checked with the help of a drug information system (Intranet-KH [V 6.0]). Of particular interest was the consumption of drugs that could favour urinary incontinence as an adverse side effect. In addition the frequency of polypharmacy and the frequency of potentially health-threatening drug combinations were registered. Results: 57 % of the patients consumed at least one drug that could reinforce urinary incontinence. The frequency of polypharmacy was 38 %. In 45 % of the patients the possibility for health-damaging interactions existed as a result of the consumed drugs. Conclusion: The frequencies of consumption of drugs that can favour urinary incontinence and of polypharmacy are high among the patients who attend a specialist outpatient department for urinary incontinence. This emphasises the importance of a complete drug history in the diagnostic work-up for urinary incontinence.
Keywords: overactive bladder; polypharmacy; urinary incontinence; drug-drug interactions